Establishment of Real-Time PCR Method to Differentiate Phlebotomus sichuanensis (Diptera, Psychodidae) from P. chinensis s.s. Based on Whole Mitochondrial Genome Analysis - Haowei Dong; Wenqi Shan; Hao Yuan; Qiuming Zhou; Wenbing Zhong; Maimaitijiang Wumaier; Kang Wang; Anjie Yang; Bing Rui; Hua Shi; Huiying Chen; Xiangyu Li; et al. (Life)
Phlebotomus sichuanensis, considered a potential vector for visceral leishmaniasis (VL), is distributed in the southern Gansu and northern Sichuan regions in China. However, the high similarity in the morphology of P. sichuanensis and P. chinensis s.s. poses unresolved taxonomic challenges. In this study, phlebotomine sand flies were collected from three locations in the southern Gansu and northern Sichuan regions (SCB group) and three locations that are the dominant distribution areas of P. chinensis s.s. (ZHB group). Their whole mitochondrial genomes were sequenced and analyzed. The differential analysis revealed that there were 339 fixed differential sites in the mitochondrial genome-coding region of P. chinensis s.s. and P. sichuanensis, among which the COI gene had the most differential sites (57), followed by ND5 (46), ND4 (38), and CYTB (37), while ATP8 had the least differential sites (4). The molecular genetic p-distance was calculated based on 13 protein-coding regions, and the genetic distance ranged from 0.001 to 0.018 in the ZHB group and from 0.001 to 0.006 in the SCB group, while the interspecies molecular genetic distance was 0.464–0.466 between the two groups. A phylogenetic maximum likelihood tree was constructed from 16 samples via tandem sequence of 13 protein-coding regions, and the topology showed that the ZHB and SCB groups formed separate clusters. A real-time PCR method was established based on the differences in the COI fragment, which can identify P. sichuanensis from P. chinensis s.s. effectively. This study presents objective evidence of the genetic differentiation between P. sichuanensis and P. chinensis s.s., and provides a method for identifying these two morphologically highly similar VL-transmitting sandflies.